(untitled) (Multidisciplinary Journal of Science and Technology, 2023)
Preliminary results of molecular genetic studies of the Bushuev cattle breed, which is on the verge of extinction, are presented as part of the scientific and practical project “Development of molecular panels for genetic certification of unique breeds of animals.”The project is being carried out with the aim of preserving the valuable gene pool of the Bushuev breed, the only one bred in Uzbekistan, developing molecular panels for genetic certification and early prediction of breeding and productive qualities of animals. In molecular genetic studies, which are being carried out on cattle for the first time in the republic, microsatellite DNA markers (short tandem repeats (STR), SNP and InDel markers) will be used. At the first stage, stud bulls of the state breeding enterprise “Uznaslchilik” were selected for research and used for semen selection. Blood samples were taken from animals. Amplification of DNA fragments was carried out using the Rotor-Gene Q software apparatus from QIAGEN Hilden, Germany. Using invitrogen reagents from Thermo Fisher Scientific (USA), DNA from the blood of Bushuev breed bulls was isolated.Preliminary findings have shown that the higher the level of purebred, the higher the genetic potential of the animals. Final conclusions based on the results of molecular genetic studies will be made after genotyping of animals is completed. Molecular genetic research continues.